Insect Microbial Symbionts: Ecology, Interactions, and Biological Significance - Sankhadeep Mondal; Jigyasa Somani; Somnath Roy; Azariah Babu; Abhay K. Pandey (Microorganisms, 2023)
The guts of insect pests are typical habitats for microbial colonization and the presence of bacterial species inside the gut confers several potential advantages to the insects. These gut bacteria are located symbiotically inside the digestive tracts of insects and help in food digestion, phytotoxin breakdown, and pesticide detoxification. Different shapes and chemical assets of insect gastrointestinal tracts have a significant impact on the structure and makeup of the microbial population. The number of microbial communities inside the gastrointestinal system differs owing to the varying shape and chemical composition of digestive tracts. Due to their short generation times and rapid evolutionary rates, insect gut bacteria can develop numerous metabolic pathways and can adapt to diverse ecological niches. In addition, despite hindering insecticide management programs, they still have several biotechnological uses, including industrial, clinical, and environmental uses. This review discusses the prevalent bacterial species associated with insect guts, their mode of symbiotic interaction, their role in insecticide resistance, and various other biological significance, along with knowledge gaps and future perspectives. The practical consequences of the gut microbiome and its interaction with the insect host may lead to encountering the mechanisms behind the evolution of pesticide resistance in insects.